The Harmonising Social Capital and Community Pariticipation in Puncu Village : A Digital Approach to Mitigating The Threat of Mount Kelud’s Eruption - Muhamad Khoirul Anam; Ferdian Dhanino Rachmawan; Muhammad Rafif Habiburrahman (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
Puncu Village, situated in the high risk zone of Mount Kelud, continues to face significant volcanic threats that necessitate effective and locally relevant disaster mitigation strategies. This study investigates how the integration of social capital and community participation can support the development of a digital mitigation model rooted in the social fabric of the community. Employing a qualitative case study approach, data were obtained through in-depth interviews, nonparticipant observation, and document analysis. The analysis was conducted using content analysis, relational content analysis, and descriptive qualitative methods. The findings indicate that elements of social capital such as mutual trust, norms of cooperation, and strong social networks serve as crucial foundations for inclusive preparedness. Nevertheless, the current level of community participation is limited to the stage of information sharing, suggesting minimal involvement in digital-based mitigation processes. The proposed strategy seeks to design a digital system that is inclusive, culturally relevant, and responsive to the lived experiences of the local population. This research highlights the need to balance technological innovation with social values to build a sustainable disaster mitigation framework in volcanic risk areas such as Puncu Village.